DESKRIPSI PISANG BERANGA PADA DUA HABITAT YANG BERBEDA - Zainal Arifin; Micha S. Ratu-Rihi (Partner, 2008)
This research was conducted from September to December 2005 in Ende (Flores) and Kupang (Timor). The aims of this research were to describe the morphology of growth of banana and production of banana fruits especially variety of Baraga, Â identify the environment of growth, and analyze the nutrient content of fruits, especially, variety of Baraga, cultivated in the two different locations. The morphology growth of Baraga cultivated in Ende was rapidly than Baraga cultivated in Kupang. The contents of vitamin C, fat, and protein showed significant differences. These differences possibly were caused by the different characteristic of land geomorphology, main material of landform, fertility of soil, especially, pH and availability of phosphor.Keywords: Description, Banana Variety of Baraga, Two Different Habitats